Studies on Effect of Temperature on Curd Yield under Year Round Production System of Cauliflower (Brassica oleracea var. botrytis L.) under Mid Hills of Himachal Pradesh - Singh Thakur, Bhupinder (International Journal of Bio-resource and Stress Management, 2023)
The cauliflower early group variety ‘Pusa Himjyoti’, mid group variety ‘Swati’ and late group variety ‘PSB K -1’ were planted at a gap of one month at different planting dates for two consecutive years during 2009-10 and 2010-11 to study the effect of varying temperatures on net curd yield and other associated characters in each maturity group. The varieties varied in their performance for net curd yield as per the maturity group and temperature regime. Early maturing varieties gave high net curd yield under high temperature planting dates whereas mid late and late maturing varieties gave high net curd yield under the mild/low temperature regimes. Curd diameter in early cauliflower was found to be maximum under increasing temperatures whereas mild temperature range helped in producing maximum curd size in mid group variety. Late group variety also produced maximum curd diameter when temperature increased from freezing to 10-15oC. The plant leaf number plant-1 was found to be highest under higher temperatures in all the maturity group varieties. Cauliflower curds irrespective of maturity group took more time to maturity at lower temperatures as compared to the high temperatures for every maturity group and planting date.